2017
DOI: 10.1136/bmjopen-2016-013346
|View full text |Cite
|
Sign up to set email alerts
|

Trends and changes in paediatric tonsil surgery in Sweden 1987–2013: a population-based cohort study

Abstract: ObjectivesThe objective of this study was to longitudinally describe the history of tonsil surgery in Swedish children and adolescents regarding incidence, indications for surgery, surgical methods and the age and gender distributions.SettingA retrospective longitudinal population-based cohort study based on register data from the Swedish National Patient Register (NPR) and population data from Statistics Sweden.ParticipantsAll Swedish children 1–<18 years registered in the NPR with a tonsil surgery procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 31 publications
2
36
0
4
Order By: Relevance
“…The incidence of infectious indications remained relatively stable. Similar findings have been published in other studies [18][19][20], reflecting an increased awareness of upper airway obstruction. TT is mostly performed because of obstructive symptoms, although a few studies have shown that TT can be beneficial also for children and young adults with recurrent tonsillitis [21,22].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The incidence of infectious indications remained relatively stable. Similar findings have been published in other studies [18][19][20], reflecting an increased awareness of upper airway obstruction. TT is mostly performed because of obstructive symptoms, although a few studies have shown that TT can be beneficial also for children and young adults with recurrent tonsillitis [21,22].…”
Section: Discussionsupporting
confidence: 91%
“…During the period from 2007 to 2016 approximately 500 tonsil surgeries were performed every year for children at our department. The incidence of tonsil surgeries remained relatively stable, in contrast to Sweden, where the rate of tonsil surgery has doubled over 26 years in children and adolescents [18]. A potential explanation for this difference is that tonsil surgeries in the Helsinki area are performed partly by the private sector, and hence, the exact number of tonsil surgeries is not known.…”
Section: Discussionmentioning
confidence: 95%
“…Surgery performed on this immune defence system remains the most common surgical procedure in children, with the highest rate of interventions between 3 and 5 years of age. Surgical indications for this procedure have varied over the years, although they focus on the prevention of recurrent infections and the treatment of OSAS.…”
Section: Introductionmentioning
confidence: 99%
“…4 In addition, in both adults and paediatric populations there is clear evidence of the association between obstructive sleep apnoea-hypopnea syndrome (OSAS) linked to tonsillar hypertrophy and systemic inflammatory phenomena, as well as an increased risk of cardiovascular disease in adulthood. 5,6 Surgery performed on this immune defence system remains the most common surgical procedure in children, [7][8][9] with the highest rate of interventions between 3 and 5 years of age. Surgical indications for this procedure have varied over the years, although they focus on the prevention of recurrent infections and the treatment of OSAS.…”
mentioning
confidence: 99%
“…TE is an effective treatment for SDB, as shown in a number of studies, but it has the disadvantages of postoperative morbidity including pain, hemorrhage, and infection . Therefore, partial or subtotal removal of the tonsils, tonsillotomy (TT), has gained popularity in recent decades . In several studies, compared with TE, TT has been shown to be associated with a lower risk of postoperative morbidity including postoperative pain and hemorrhage .…”
Section: Introductionmentioning
confidence: 99%